Body composition in men with anorexia nervosa: Longitudinal study. Issue 7 (29th April 2017) - El Ghoch, Marwan; Calugi, Simona; Milanese, Chiara; Bazzani, Paola Vittoria; Dalle Grave, Riccardo
Abstract: Objective: To compare body composition patterns before and after complete weight restoration in men with anorexia nervosa. Method: Dual‐energy X‐ray absorptiometry (DXA) was used to measure body composition patterns in 10 men with anorexia nervosa before and after complete weight restoration, and in 10 healthy men matched to age and patients' post‐treatment body mass index (BMI). Results: Before weight restoration, men with anorexia nervosa displayed lower total body fat mass (FM) and lean mass (LBM) than those in the healthy comparison group, with a greater FM loss from the extremity than the trunk region. After short‐term weight restoration, patients displayed complete normalization in total LBM and FM, but greater deposition of FM in the trunk region. Conclusion: Short‐term weight restoration can normalize body composition patterns in men with anorexia nervosa, but results in a central adiposity phenotype. The clinical implication of this finding is unknown, but should be explored given the high levels of concern about central adiposity in anorexia nervosa.